2003
DOI: 10.2337/diacare.26.4.1052
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis of Young Adults With Type 1 Diabetes

Abstract: OBJECTIVE -To determine the role of early behavioral and psychological factors on later outcomes in young adults with childhood-or adolescent-onset type 1 diabetes.RESEARCH DESIGN AND METHODS -We conducted a longitudinal cohort study of patients recruited from the register of the young adult outpatient diabetes clinic, Oxford, U.K. A total of 113 individuals (51 male subjects) aged 17-25 years completed assessments, and 87 (77%) were reinterviewed as older adults (aged 28 -37 years). Longitudinal assessments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
282
1
19

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(310 citation statements)
references
References 25 publications
8
282
1
19
Order By: Relevance
“…[8][9][10][11][12] It is critical to maintain BG monitoring frequency through this developmental stage since it has been demonstrated that those with poor adjustment to diabetes in adolescence are likely to continue such behaviors into adulthood. 13,14 Increased involvement with healthcare providers may improve glycemic control and reduce the risk of complications, 15 but these interactions are labor-intensive and expensive. Low-cost clinic-based interventions in younger adolescents have yielded a positive impact on both glycemic control and quality of life.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] It is critical to maintain BG monitoring frequency through this developmental stage since it has been demonstrated that those with poor adjustment to diabetes in adolescence are likely to continue such behaviors into adulthood. 13,14 Increased involvement with healthcare providers may improve glycemic control and reduce the risk of complications, 15 but these interactions are labor-intensive and expensive. Low-cost clinic-based interventions in younger adolescents have yielded a positive impact on both glycemic control and quality of life.…”
mentioning
confidence: 99%
“…After 11 years of DM existence, the prevalence of some degree of DR is around 66.6%, 23 increasing to approximately 100% after 20 years of DM. 24 Recently, a Brazilian group described a prevalence of 21% to DR in a sample of 81 type 1 DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The paediatric diabetes community has mobilised itself to meet this challenge, but faces the problem that puberty is typically followed by a sharp rise in HbA 1 c and that inadequate control, once established, tends to persist into later life. A follow-up study of teenagers with type 1 diabetes in the UK found that HbA 1 c was unchanged (8.6% in men, 8.7% in women) after 11 years of follow-up, whilst the proportion with serious complications rose from 3 to 37% and psychiatric disorders increased from 16 to 28% [18]. The reasons for poor glucose control in adolescence range from the endocrine and physiological to the social, emotional and psychological; complicated by the natural inclination of young people to assert their autonomy in the face of parental and other constraints.…”
mentioning
confidence: 99%